The Nature of Science Aspects That High School Students Exhibit During Debating a Controversial Socio-scientific Issue - TAHER, REHAM EMAD MAHFOUZ (2017)
Over the last century, a lot of investigations were done to enhance the students’ understanding of the nature of the scientific knowledge, as well as, to have the educators agreed to put the nature of the scientific knowledge at the center of the scientific literacy. Effective scientific literacy development in our students requires linking science to the society, and allowing the students to explore the scientific knowledge while dealing with the challenges of the real world. The purpose of this study is to explore how students comprehend science, especially in its tentative, subjective, and social/cultural embedded nature. This study was carried on a group of sixty students of twelfth grade, following their debate about a socio scientific issue, in which a qualitative design was used to collect the data. The tools used were open-ended questionnaire, and one-to-one interviews in order to clarify their conceptions about the nature of the scientific knowledge. Results specified that the participants had good understanding of the nature of the scientific knowledge categories intended to be explored; in addition, this study recommended using scientific argumentation of socio- scientific issues as an effective tool in enhancing the students understanding of the nature of science.